THE ROLE OF THE NATIONAL EYE BANK IN THE DEVELOPMENT OF KERATOPLASTY SERVICES IN AZERBAIJAN - Gasimov E.M.; Hasanov J.V. (The Azerbaijan Journal of Ophthalmology, 2026)
Purpose – to analyze keratoplasty indications, surgical trends, and the quality parameters of imported donor tissues in Azerbaijan, and to evaluate the necessity of establishing a National Eye Bank.Material and methodsA retrospective analysis of keratoplasty indications and surgical techniques performed between 2008 and 2024 was conducted. Additionally, demographic characteristics, time intervals, and endothelial cell density (ECD) of 272 donor corneas imported from the USA between 2018 and 2025 were evaluated.ResultsIn 2022, a total of 3,659 corneal pathologies were registered at the National Ophthalmology Centre named after Academician Zarifa Aliyeva and its affiliated tertiary centres. The most common indications were aphakic and pseudophakic bullous keratopathy (ABK/PBK) (24.5%) and keratoconus (19.6%). Among the imported donor corneas, the mean donor age was 60.2 ± 1.2 years, and the mean ECD was 2602 ± 35.5 cells/mm2. The preservation-to-surgery interval was 11.2 ± 0.17 (4-14) days. Although all parameters met international standards, prolonged storage duration may contribute to cumulative endothelial cell loss.ConclusionThe establishment of a National Eye Bank in Azerbaijan represents a clinical and strategic necessity for the sustainable and high-quality development of keratoplasty services.